Convenções processuais em lides tributárias: instrumento de política pública consensual para recuperação do crédito tributário - Rennó, Gabriela Machado (2021)
The study aims to analyze the consensual public policy of active debt collection, with a focus on Procedural Legal Businesses (NJPs) signed at the federal level, with a view to collecting scientific evidence on the phenomenon studied. The question that we intend to answer, under the theoretical understanding of collaborative law and consensuality as a duty of action of good public administration, is to measure whether consensual action, through the NJPs, generates efficiency for federal tax collection, with benefits to the taxpayer and the Public Administration, to subsidize specific regulation of such practice by the State of Goiás. To answer it, consensuality is analyzed in a theoretical, normative and empirical way. In the first part, we seek to establish the theoretical and normative paradigms that underlie the dialogic tax collection, running over relevant points, such as the unavailability of public credit and the slowness of tax executions. Then, empirically, the second part of the dissertation is intended to map the NJPs signed by the Attorney General of the National Treasury, indicating descriptive statistical analysis of data and scientific evidence on the use of procedural conventions in tax matters. The reality of tax consensuality in the State of Goiás is also analyzed, in order to assess the increase in consensuality, state limitations and opportunities. In this part, the main impasses related to judicial tax collection and the form of employment of the NJP are assimilated, in order to verify the effects of consensuality in Tax Law through the specific mechanism. In the third part, finally, the practical plan of consensual tax collection in the State of Goiás is evaluated, using the federal experience to support good performance practices at the state level, through the methodology of ex ante evaluation of public policy. In conclusion, finally, the problem that motivated the research is resumed, with a view to revisiting the hypotheses tested in the work and providing practical subsidies to be used by the State Attorney of Goiás in the institutionalization of procedural conventions in tax matters. It is concluded that specific regulation by public entities is recommended and the use of procedural conventions needs to be encouraged to implement the Public Judiciary Policy for the proper resolution of conflicts, contributing to the reduction in tax litigation and to the increase in the collection of public safes.